Finding hard evidences for the soft rhetoric of the stakeholder theory - Bocatto, Evandro; Perez-de-Toledo, Eloisa (My University, 2018)
The hard-science type of rhetoric present in the dominant model in management is put under scrutiny. As a result, the shareholders' profit maximization ideal is understood as just a competing socially constructed rhetoric. We are motivated by: 1. why is it taken for granted that the dominant model of business activity is scientific? and, 2. How the competing stakeholder approach would look like? We present mathematical equations that capture other constructs (e.g. women and employee participation, CSR, CER) and propose a stakeholder index (GOV-Icompr). Results indicate that companies that include other stakeholders have superior market value (measured by Tobin 's q).
Keywords: stakeholder theory; employee participation in management; market value; stakeholders; mathematical models